Financial Reporting Quality and Firms’ Market Value during Accounting and Disclosure Regime Change: The Case of Malaysia - Chia Hua, Sim (UNIMAS, 2023)
In emerging economy contexts like Malaysia, researchers noted that distinct political and cultural elements mix with micro- and macroeconomic pressures to influence firms' compliance culture, financial reporting, regulatory risk management, and market value. One may expect that financial statements and other legislative requirements will provide market participants with value-relevant information. However, prior research reveals that Malaysia's high concentration of ownership, close ties between corporations and banks as well as insider governance may lead to a decrease in the desire for public financial reporting, with asymmetric information issues settled via private communication channels. In search of justification for the economic benefits of investing effort and resources for a closer engagement with accounting and disclosure regime change, this study examines whether Malaysia’s market values the quality of financial reporting by listed firms.